Use of bacteriophage as an antimicrobial in food products - Bassett, Kelly D (Kansas State University, 2007)
Food recalls and incidence of foodborne disease are on the rise throughout the world. Food products are recalled in the United States almost daily, and typically a large quantity of food is affected. Pathogenic microorganisms are readily invading the food supply and traditional methods and use of antimicrobials are not performing as well as in the past. The microorganisms that prompt the recalls cause symptoms ranging from mild gastroenteritis to death. All humans eat food, therefore all humans have the potential to be exposed to pathogens in food at some point in their life. There is a need for new, more effective antimicrobials for use on food products in order to ensure that consumers have access to a safe food supply. Any new treatments for prevention of pathogenic growth in the food supply should be researched. Phage preparations used as antimicrobials on food products are a novel idea. Phages are advantageous over traditional antimicrobials such as antibiotics, pesticides, and sanitizers in numerous ways. This report presents the history of phage and phage therapy in humans, advantages and disadvantages of phage use over traditional methods, current phage preparations available or under research, and approvals and objections of phage use in the food supply.
Keywords: Bacteriophage; Food borne illness; Biology, Microbiology (0410)